Clinical evaluation versus magnetic resonance imaging findings in patients with radicular arm pain—A pragmatic study. Issue 3 (10th April 2022) - Redebrandt, Henrietta N.; Brandt, Christian; Hawran, Said; Bendix, Tom
Abstract: Objectives: Cervical nerve root compression can lead to radiculopathy in the arm. Some studies have reported low accuracy in determining the responsible nerve root in both cervical and lumbar regions. This prospective, observational, pragmatic study aimed to determine the accuracy of the clinical evaluation relative to magnetic resonance imaging (MRI) findings in patients with arm radiculopathy. Methods: Patients with neck pain and neck‐related arm pain referred to a spine unit underwent a standard clinical neurological examination and cervical spine MRI. The clinical examination required a judgment of the most likely cervical root involved, including the side. The Interobserver reproducibility was tested. Using MRI, the most likely nerve root involved according to radiology was assessed. Results: Eighty‐three patients met the inclusion criteria. The Interobserver reproducibility between clinical evaluators was 58%, with a modest κ coefficient (0.33, 95% confidence interval [CI]: 0.18–0.47) classified only as "fair agreement." Only 31% (95% CI: 22–42) of the 83 patients exhibited full agreement regarding the suspected cervical root as assessed via the clinical evaluation and MRI. In another 28% (95% CI: 18–39), the clinical evaluation identified an adjacent level to that identified on MRI. Conclusions: In cervical radiculopathy, the clinical‐neurological examination diagnosed the same in 31% or an adjacent cervical root in 28% of the patients in relation to the most affected cervical root on MRI.